MOBILITAS MURSYID CUM-AKTIVIS DALAM TRADISI TAREKAT - Ahmadi, Rizqa; Hefni, Wildani (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2019)
Â This article elaborates on the role and movement of murshid as an informal institution in the tarekat, which is at the same time an integral part of the Sufism tradition. By using a socio-historical approach, this article identifies the intellectual movement of murshid in reproducing and reformulating strong beliefs as a connector of scientific transmission traditions (sanad), which are convened into two categories. First, the movement that interprets murshid activism in terms of their personal characteristics, such as their thoughts that play its function in regulating some religious aspects, especially as a reference for the followers. Second, the musrhid movement that links a structure into social functions, for example creating, disseminating, and carrying out culture. Murshid in this category is identified as the holder of scientific sanad that have vertical mobility to save the world so that it does not become a prison for individuality. This category of murshid charisma can be the foundation of the followers of the tarekat to avoid a lot of false information, the spread of hoax news from social media, and various other noises in this post-truth era.